Change in Maslow’s hierarchy of basic needs: evidence from the study of well-being in Mexico - Méndez, Alfonso; Rojas, Mariano (Anales de Psicología / Annals of Psychology, 2024)
Maslow’s pyramid is a symbol that has endured in the image of psychologists, scientists, businessmen and politicians around the world; its premise expresses a hierarchy of needs, but sometimes this idea is confused with sequentiality and ascendancy of satisfaction that begins with physiological needs and ends with self-actualization. This article examines empirically the hierarchy of basic needs from the perspective of subjective well-being in Mexico. The analyzes are carried out with a sample of 38,560 cases from the Mexican population, using a stepwise forward multiple linear regression model. The main finding is that the needs for love and belonging are the ones that explain satisfaction with life to a greater degree, the hierarchy proposed by Maslow changes insofar as its importance for subjective well-being. The relevance of belonging needs as explanatory factor of well-being in Mexico is discussed.